Effect of Fermentation with Two Molds on Characteristics of Chicken Meat - Liping Guo; Yan Li; Shengchao Ding; Baowei Wang; Yinglian Zhu; Bin Pang; Ming Huang; Harvey Ho; Jiying Yu; Jingxin Sun (Journal of Food Quality)
In the present study, we investigated the characteristics of chicken meat fermented with Penicillium nalgiovense and Penicillium chrysogenum. Hardness and springiness gradually decreased, while gumminess gradually increased during fermentation. Fermentation with P. chrysogenum led to higher hardness and lower gumminess than fermentation with P. nalgiovense. Fermentation with two molds resulted in similar microstructure, such as granule formation and fractured myofibril. The highest percentage of secondary structure was ɑ-helix, and tyrosine residues were buried after fermentation. P. nalgiovense-fermented samples contained more bound water, lower relative content of alkanes, and higher relative content of aldehydes than P. chrysogenum-fermented samples.